Preparation method of bismuth-silicon nanowire compound catalyst

By combining bismuth with silicon nanowires to form a bismuth-silicon nanowire composite catalyst, the problem of insufficient catalytic activity and selectivity in the CO2 reduction reaction is solved, the effect of efficient production of formic acid is achieved, and the cost of the catalyst is reduced.

CN120231087APending Publication Date: 2025-07-01苏州市商祺光电有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510423332.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing electrocatalysts have insufficient catalytic activity and selectivity in CO2 reduction reactions, and are costly and scarce, making it difficult to achieve large-scale application.

Method used

Silicon nanowires are used as support, and bismuth and silicon nanowires are combined through a preparation method to form a bismuth-silicon nanowire composite catalyst for electrochemical CO2 reduction reaction.

Benefits of technology

This catalyst can produce formic acid efficiently, with a Faraday efficiency up to 91%. The Faraday efficiency of formic acid production in the range of -0.8 to -1.2 V vs RHE is around 85%, and it is low in cost and rich in resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120231087A_ABST
    Figure CN120231087A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bismuth-silicon nanowire compound catalyst, which is characterized in that the bismuth-silicon nanowire compound catalyst comprises the following raw materials: silicon nanowires, H2O, Bi (NO3) 35H2O and HF solution or NH4F solution; the preparation method comprises the following steps: adding Bi (NO3) 35H2O into an aqueous dispersion of a silicon nanowire, then adding one of an HF solution or an NH4F solution for reaction, centrifuging the obtained product, then washing the product with ethanol and water, putting the product into a freeze-drying oven for freeze-drying, and collecting a black powder sample to obtain the bismuth-silicon nanowire compound catalyst. The bismuth-silicon nanowire compound catalyst is synthesized by adopting the silicon nanowire as a carrier and a one-step method, so that the cost of the catalyst is remarkably reduced; when the catalyst is used for electrochemical CO2 reduction catalytic reaction, formic acid can be efficiently produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalysts, and particularly relates to a preparation method of a bismuth-silicon nanowire composite catalyst. Background Art

[0002] Converting CO2 into high-value carbon-containing organic compounds through an electrochemical reduction reaction can effectively solve the greenhouse effect and environmental problems. However, due to factors such as the inertness of CO2 itself, the sluggish multi-electron transfer kinetics involved in the reduction process, and the competitive hydrogen evolution reaction during the CO2 reduction process, most electrocatalysts are difficult to obtain ideal catalytic activity and high product selectivity.

[0003] Currently, the main problems in the selection of electrocatalysts are: (1) Precious metals are scarce and expensive, making it difficult to be applied on a large scale. (2) Short cycle life and insufficient stability. (3) Poor product selectivity and high reaction overpotential. Therefore, developing a CO2 reduction electrocatalyst that is both highly active and selective, low-cost, highly efficient, and abundant in reserves on the earth has important practical significance for large-scale production applications.

[0004] Bismuth-based materials are inexpensive and less toxic, and are an efficient CO2 reduction electrocatalyst. Its main catalytic products are CO and formic acid. Compared with CO, formic acid is a liquid and is easy to store. It is also an important chemical intermediate in many industrial production processes and is widely used in energy and industrial fields such as hydrogen storage and fuel cells. It is a more ideal target product. Therefore, improving the selectivity and activity of bismuth-based catalysts towards formic acid is the key technical difficulty in the development of commercial applications.

[0005] Due to the relatively low melting point of metallic bismuth itself and its susceptibility to oxidation, it is difficult to directly prepare a single-metal bismuth catalyst with a nanostructure using conventional methods. At the same time, bismuth-based materials have poor electrical conductivity. The electrocatalytic reduction ability of a single-component bismuth-based electrocatalyst material is limited by its own structure and other factors. Therefore, a large number of reports have proposed constructing composites or alloys by combining metallic bismuth with highly conductive carbon carriers or various metals to improve catalytic activity. However, the introduction of carbon materials may change the selectivity of bismuth-based materials towards formic acid, and the introduction of other metals increases the preparation cost of the catalyst. Summary of the Invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a preparation method of a metallic bismuth-based catalyst.

[0007] In order to achieve the above technical effects, the technical solution adopted by the present invention is: A preparation method of a bismuth-silicon nanowire composite catalyst, characterized by comprising raw material silicon nanowires, H2O, Bi(NO3)3∙5H2O, and an HF solution or an NH4F solution; the preparation method is to add Bi(NO3)3∙5H2O to an aqueous dispersion of silicon nanowires, and then add one of the HF solution or the NH4F solution to react, centrifuge the obtained product, wash it with ethanol and water, and then put it into a freeze-drying oven for freeze-drying, and collect the black powder sample to obtain the bismuth-silicon nanowire composite catalyst.

[0008] Preferably, the preparation method is as follows: Disperse 30 mg of silicon nanowires in 10 mL of H2O, then add no more than 1 mL of 0.05 M Bi(NO3)3∙5H2O solution, and then add 0.5 mL of 5% HF solution. React under ultrasonic conditions for 0.5 h and then centrifuge. Wash the obtained product with ethanol and water, put it into a freeze-drying oven for freeze-drying for 12 h, and collect the black powder sample to obtain the bismuth-silicon nanowire composite catalyst. More preferably, the Bi(NO3)3∙5H2O solution is 0.25 mL, 0.5 mL or 0.75 mL.

[0009] Preferably, the preparation method is as follows: Disperse 30 mg of silicon nanowires in 10 mL of H2O, then add no more than 1 mL of 0.05 M Bi(NO3)3∙5H2O solution, and then add 20 mL of 40% by mass NH4F aqueous solution. Pour the dispersion into a hydrothermal reaction kettle and react at 110 °C. Control the reaction time to 2 h. Centrifuge the obtained product, wash it with ethanol and water, put it into a freeze-drying oven for freeze-drying for 12 h, and collect the black powder sample to obtain the bismuth-silicon nanowire composite catalyst.

[0010] Preferably, the silicon nanowires are prepared by the oxide-assisted method, and the steps are as follows: Load silicon monoxide powder into an alumina porcelain boat, then place the alumina porcelain boat horizontally at the center of an alumina tube, and then place the alumina tube into a high-temperature tube furnace; Pump the tube furnace to a pressure of 100 Pa, and then raise the temperature of the tube furnace to 1300 °C and keep it warm for 1 h; After reaching the predetermined time, cool it naturally to room temperature, and collect the silicon nanowires grown on the inner wall of the alumina tube.

[0011] A bismuth-silicon nanowire composite catalyst, characterized in that the bismuth-silicon nanowire composite catalyst is prepared by the above preparation method.

[0012] A method for catalytic production of formic acid by CO2 reduction, characterized in that the catalyst used in the method for producing formic acid is a bismuth-silicon nanowire composite catalyst, which is prepared by the above preparation method.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention uses silicon nanowires as a carrier and synthesizes a bismuth-silicon nanowire composite catalyst by a one-step method. When used in an electrochemical CO2 reduction catalytic reaction, it can efficiently produce formic acid. In addition, silicon is the second most abundant element in the earth's crust, with a wide source and low price. Using silicon nanowires as a carrier significantly reduces the cost of the catalyst. In a three-electrode H-type electrolytic cell system, the Faraday efficiency of the bismuth-silicon nanowire composite catalyst for formic acid reduction can reach up to 91%. In the range of -0.8 to -1.2 V vs RHE, the Faraday efficiency of formic acid production is about 85%. Silicon nanowires can obtain elemental bismuth by reducing silicon-hydrogen bonds, and at the same time provide an anchoring site for elemental bismuth, limiting the size of nanobismuth and increasing the number of active sites. The amorphous silicon oxide layer spontaneously formed on the silicon surface can inhibit the hydrogen evolution reaction, stabilize the intermediate *OCHO, and promote the formation of formic acid.

[0014] The above description is only an overview of the technical solution of the present invention. In order to understand the technical means of the present invention more clearly, it can be implemented according to the content of the specification. And in order to make the above and other purposes, features and advantages of the present invention more obvious and understandable, the present invention will be further described in detail below with reference to the drawings and embodiments. Obviously, the described embodiments are some embodiments of the present invention, rather than all embodiments. Brief Description of the Drawings

[0015] Figure 1a and 1b are TEM images of Bi-Si-0.50 at different magnifications; Figure 1c is the EDS energy spectrum curve of Bi-Si-0.50; Figure 1d is the HRTEM image of Bi-Si-0.50; Figure 1e is the EDS surface scan image of Bi-Si-0.50: Figure 2a are XRD patterns of Bi-Si samples with different Bi contents; Figure 2b is the XPS full spectrum of Bi-Si-0.50; Figure 2c is the Bi 4f fine spectrum of Bi-Si-0.50; Figure 2d is the Si 2p fine spectrum of Bi-Si-0.50; Figure 3a is the LSV curve of the Bi-Si-0.50 catalyst in N2 and CO2-saturated KHCO3 electrolytes; Figure 3bi-t curves of Bi-Si-0.50 at different potentials in CO2-saturated KHCO3 electrolyte; Figure 3c Bar chart of Faraday efficiency of different products of Bi-Si-0.50; Figure 3d Partial current curve of formic acid and Faraday efficiency diagram of HCOOH during the stability test of Bi-Si-0.50 for CO2 reduction; Figure 4 Comparison chart of Faraday efficiency for the catalytic reduction of CO2 to produce HCOOH by Bi-Si-0.25, Bi-Si-0.50 and Bi-Si-0.75 catalysts with different Bi contents. Detailed implementation method Example 1

[0016] A preparation method of a bismuth-silicon nanowire composite catalyst. First, 30 mg of silicon nanowires are dispersed in 10 mL of H2O, then 0.25, 0.50, 0.75 mL of 0.05 M Bi(NO3)3∙5H2O solution are added respectively, and then 0.5 mL of 5% (mass fraction) HF solution is added. After reacting for 0.5 h under ultrasonic conditions, centrifugation is carried out, and then the product is washed several times with ethanol and water, and placed in a freeze-drying oven for 12 h, and then a black powder sample is collected to obtain a bismuth-silicon nanowire composite catalyst.

[0017] In this example, the obtained bismuth-silicon nanowire composite catalysts are named Bi-Si-0.25, Bi-Si-0.50, Bi-Si-0.75 according to the dosage of Bi(NO3)3∙5H2O; then electrochemical tests are carried out respectively. All electrochemical experiments are tested using a Shanghai Chenhua CHI 760 E electrochemical workstation. The test uses a traditional three-electrode system. In 0.5 M KHCO3 solution, a saturated calomel electrode and a platinum sheet (1 × 1 cm 2 ) are used as the reference electrode and the counter electrode, and the working electrode is a carbon paper modified with the catalyst (the catalyst modification area is 1 × 1 cm 2 ). The preparation process of the working electrode is as follows: Take 4 mg of the catalyst and ultrasonically disperse it in 1000 µL of Nafion (0.5 wt%) solution for 0.5 h, and then take 50 µL and evenly drop it on the surface of the carbon paper and let it dry naturally. The catalyst loading is 200 µg cm −2 .

[0018] The measurements of product analysis were carried out in a closed H-type electrochemical cell. The two chambers were separated by a proton exchange membrane (NR212). The electrolyte in each chamber was 35 mL of 0.5 M KHCO3, and the volume of the upper gas was 30 mL. The possible carbon-containing gas products (such as CO, CH4, C2H4, and C2H6) were tested using a flame ionization detector (FID) and a TDX-1 column with a methane converter. The by-product H2 was detected using a thermal conductivity detector (TCD) and a molecular sieve 5A packed column. The liquid-phase products were studied using a Bruker Avance III - 400 nuclear magnetic resonance spectrometer. 0.5 mL of the electrolyte was mixed with 0.1 mL of D2O (anhydrous), and 0.05 μL of dimethylaniline (DMSO, Sigma, 99.99%) was added as an internal standard for testing. The working electrode and the reference electrode were in the cathode chamber, and a platinum plate electrode was used as the counter electrode in the anode chamber.

[0019] First, the morphology of the Bi-Si catalyst was characterized by electron microscopy. Figure 1a The transmission electron microscope (TEM) image of the silicon wire modified with Bi (Bi-Si-0.50) is shown. The silicon wire maintained its linear morphology, and bismuth nanoparticles were uniformly loaded on its surface. The particles were small and uniform, with an average size of about 7.8 nm (see Figure 1b ). The presence of Si and Bi elements was observed from the energy-dispersive X-ray spectroscopy (EDS) (see Figure 1c ). The C and O elements originated from the adsorption and partial oxidation on the sample surface. The Cu element originated from the microgrid film supporting the sample during the test. In the high-resolution transmission electron microscope (HRTEM) image ( Figure 1d ), the lattice spacing of the (111) plane of silicon was clearly seen to be 0.313 nm, and the lattice spacing of the (104) plane of Bi was 0.236 nm. At the same time, the presence of an amorphous oxide layer could also be observed on the material surface. The surface scan of the EDS spectrum of the Bi-Si-0.50 catalyst was carried out ( Figure 1e ), and it could be further confirmed from the element distribution map that the Bi particles grew on the surface of the silicon nanowires.

[0020] Next, the X-ray powder diffraction (XRD) patterns of different Bi contents were tested, as shown in Figure 2a As the Bi in the raw material 3+With the increase of the content, the peak of Bi is enhanced and the peak of Si is weakened. The peaks located at 28.4, 47.3 and 56.1° correspond to the (111), (220) and (311) planes of Si, and the remaining peaks located at 27.2, 37.9, 39.6, 48.7, 55.6, 62.2 and 64.5° correspond to the (012), (104), (110), (202), (024), (116) and (122) crystal planes of Bi. No other substance peaks are observed. Combining with the analysis results of the morphology, it shows that the Bi-Si composite is successfully synthesized.

[0021] Figure 2b is the full X-ray photoelectron spectroscopy (XPS) spectrum of the Bi-Si-0.50 sample. Elements Bi, Si, C, and O exist in the sample, which is consistent with the energy spectrum results of the transmission electron microscope. The Ti element comes from the Ti sheet that supports the sample during the test. Figure 2c shows the fine spectrum of Bi 4f. The peaks with binding energies located at 163.2 and 157.8 eV correspond to the 0 4f5 / 2 and 4f7 / 2 dipole components of Bi. In addition to these two peaks, peaks located at 164.9 and 159.6 eV are also observed, corresponding to the 3+ 4f5 / 2 and 4f7 / 2 dipole components of Bi, indicating that there is an oxide layer on the surface of Bi. This is consistent with the phenomenon observed in the HRTEM image ( Figure 1d ). The fine spectrum of Si 2p is as shown in Figure 2d . The strong peak with a binding energy of 97.6 eV belongs to the peak of the silicon-silicon bond. A peak is observed at 101.8 eV, which is the peak of the silicon-oxygen bond, indicating that the surface of the Bi-Si composite is oxidized by air.

[0022] Next, the electrochemical CO2 reduction performance of the Bi-Si catalyst was tested. First, N2 and CO2 were introduced into the H-type electrolytic cell until saturation, and then the linear sweep voltammetry (LSV) curves of Bi-Si-0.50 in different atmospheres were tested. As can be seen from Figure 3a , the current density in the CO2-saturated electrolyte is significantly greater than that under the N2-saturated condition, indicating that Bi-Si-0.50 has catalytic activity for the electrochemical reduction of CO2. To further illustrate the CO2 reduction performance of Bi-Si-0.50, the catalyst was subjected to i-t testing ( Figure 3b ) at different potentials, the products were collected, and then the Faraday efficiencies of the liquid-phase product formic acid and the gas-phase products carbon monoxide and hydrogen were measured by nuclear magnetic mass spectrometry and gas chromatography, and the relevant pictures were drawn (see Figure 3c). In the voltage range of -0.8 to -1.2 V vs RHE, the Faraday efficiency of formic acid is higher than that of carbon monoxide and hydrogen, and both reach more than 80%. Especially at -1.0 V vs RHE, the Faraday efficiency reaches 91.2%. At the same time, we also tested the stability of Bi-Si-0.50 (see Figure 3d ). The partial current density curve of formic acid is relatively stable as a whole, with small fluctuations. This catalyst can maintain a Faraday efficiency of about 90% within 10 h. The silicon nanowires provide stable anchoring points for bismuth nanoparticles, preventing structural damage and particle agglomeration, making this catalyst have good stability.

[0023] Next, we also tested the CO2 reduction performance of Bi-Si-0.25 and Bi-Si-0.75 and compared them with Bi-Si-0.50 (see Figure 4 ). In the tested voltage range (-0.8 - -1.2 V vs RHE), Bi-Si-0.25 and Bi-Si-0.75 can also catalyze the production of formic acid, but the overall Faraday efficiency is lower than that of Bi-Si-0.50. Example 2

[0024] A preparation method of a bismuth-silicon nanowire composite catalyst, which is to replace the HF solution in Example 1 with an aqueous NH4F solution. Specifically: Disperse 30 mg of silicon nanowires in 10 mL of H2O, then add no more than 1 mL of 0.05 M Bi(NO3)3∙5H2O solution, and then add 20 mL of an aqueous NH4F solution with a mass fraction of 40%. Pour the dispersion into a 50 mL hydrothermal reaction kettle, react at 110 °C for 2 h, cool to room temperature, centrifuge the obtained product, wash it with ethanol and water, and put it into a freeze-drying oven to freeze-dry for 12 h, and then collect the black powder sample to obtain the bismuth-silicon nanowire composite catalyst.

[0025] The present invention is not limited to the above specific embodiments. For those of ordinary skill in the art, starting from the above concept, without creative labor, all kinds of transformations made fall within the protection scope of the present invention.

Claims

1. A method for preparing a bismuth-silicon nanowire composite catalyst, characterized in that: The invention comprises raw materials of silicon nanowires, H2O, Bi(NO3)3∙5H2O, and HF solution or NH4F solution. The preparation method comprises the following steps: adding Bi(NO3)3∙5H2O to an aqueous dispersion of silicon nanowires, and then adding one of the HF solution or NH4F solution to react, centrifuging the obtained product, washing it with ethanol and water, and then placing it in a freeze drying box for freeze drying, and then collecting a black powder sample to obtain a bismuth-silicon nanowire composite catalyst.

2. The method for preparing the bismuth-silicon nanowire composite catalyst according to claim 1, characterized in that: The preparation method is as follows: 30 mg of silicon nanowires are dispersed in 10 mL of H2O, then no more than 1 mL of 0.05 M Bi(NO3)3∙5H2O solution is added, and then 0.5 mL of 5% HF solution is added, reacting under ultrasonic conditions for 0.5 h and then centrifuging, washing the obtained product with ethanol and water, placing it in a freeze drying box for freeze drying for 12 h, and then collecting a black powder sample to obtain a bismuth-silicon nanowire composite catalyst.

3. The method for preparing the bismuth-silicon nanowire composite catalyst according to claim 2, characterized in that: The Bi(NO3)3∙5H2O solution is 0.25 mL.

4. The method for preparing the bismuth-silicon nanowire composite catalyst according to claim 2, characterized in that: The Bi(NO3)3∙5H2O solution is 0.5 mL.

5. The method for preparing the bismuth-silicon nanowire composite catalyst according to claim 2, characterized in that: The Bi(NO3)3∙5H2O solution is 0.75 mL.

6. The method for preparing the bismuth-silicon nanowire composite catalyst according to claim 1, characterized in that: The preparation method is as follows: 30 mg of silicon nanowires are dispersed in 10 mL of H2O, then no more than 1 mL of 0.05 M Bi(NO3)3∙5H2O solution is added, and then 20 mL of 40% by mass NH4F aqueous solution is added, the dispersion is poured into a hydrothermal reactor, and the reaction is carried out at 110°C. The reaction time is controlled to be 2 h, the obtained product is centrifuged, washed with ethanol and water, placed in a freeze drying oven for freeze drying for 12 h, and then a black powder sample is collected to obtain a bismuth-silicon nanowire composite catalyst.

7. The method for preparing the bismuth-silicon nanowire composite catalyst according to claim 1, characterized in that: The silicon nanowires are prepared by an oxide-assisted method, the steps of which are: loading silicon monoxide powder into an alumina porcelain boat, then horizontally placing the alumina porcelain boat at the center of an alumina tube, and then loading the alumina tube into a high-temperature tube furnace; pumping the tube furnace to a pressure of 100 Pa, then raising the tube furnace to 1300 ° C and keeping it warm for 1 hour; naturally cooling to room temperature after reaching a predetermined time, and collecting the silicon nanowires grown on the inner wall of the alumina tube.

8. A bismuth-silicon nanowire composite catalyst, characterized in that: The bismuth-silicon nanowire composite catalyst is prepared by the preparation method according to any one of claims 1 to 6.

9. A method for producing formic acid by CO2 reduction catalysis, characterized in that: The catalyst in the method for producing formic acid adopts the bismuth-silicon nanowire composite catalyst according to claim 8.